An Original Socialist Realist Novelist in the Context of the Approach to Religion in Modern Turkish Literature: Kemal Tahir - Hukum, Muhammed; Kanter, Muhammet Fatih; Unlu, Bedirhan (Mdpi, 2025)
Rationalist thought and positivism, as observed in various Eastern societies, led to significant upheavals in Turkish society concerning entrenched beliefs about the relationship between humanity and the world. These upheavals can be traced through the modernization efforts of the Tanzimat (Reorganization) period (between 1839 and 1896, the period of modernization and renewal in the Ottoman Empire). Although the initial generation of writers and poets during this period did not overtly renounce their connections to tradition, by the onset of the 20th century, a critical perspective towards traditional and religious content in both poetry and novels became evident. In its formative stages, Turkish socialist novels, which evolved under the influence of Russian socialism, were shaped by the classical Marxist interpretation of religion. Consequently, the socialist realist Turkish novel developed a more original character and distanced itself from stereotypical judgments. Kemal Tahir, who occupies a significant role in the realm of Turkish socialist novels, offers insights into the position and function of faith within society, as he transitioned from the classical Marxist paradigm towards a more original understanding. This study investigates the alterations in religious approaches during the Westernization process within Turkish literature and assesses the reflections of this transformation in the novels of Kemal Tahir (1910-1973), one of the preeminent figures of the socialist realist Turkish novel.
Keywords: Turkish literature; religion; socialist realism; Kemal Tahir